PENTINGNYA MENERAPKAN NILAI - NILAI PANCASILA DI TENGAH KEMAJEMUKAN - Farah Az Zahra, Shabrina; Najicha, Fatma Ulfatun (RONTAL: Jurnal Keilmuan Pancasila dan Kewarganegaraan, 2022)
The State of Indonesia is a unitary state blessed with diversity, which consists of race, ethnicity, religion, language and culture which form one unit, namely the Indonesian nation. This pluralism can be found in all regions in Indonesia, from Sabang to Merauke, and is an inseparable part of the Indonesian nation. With this plurality, it does not rule out the possibility of conflict due to differences. Therefore, the role of Pancasila as a nation unifier is very much needed in the midst of this pluralism. The purpose of this research is to provide information about the importance of applying Pancasila values in the midst of pluralism. This research method uses literature study by reading and gathering information from reference journals and from other reference sources that are relevant to the subject matter to be discussed.